BUILDING A SELF-CONCEPT THROUGH SOCIAL COMMUNICATION IN THE COMMUNITY - Doddy Harrybowo; Yusna Wulan Sari Tanjung (SEAN Institute, 2020)
This research is a qualitative research that aims to describe the self-concept through social communication among the people of Cikondang Village, Sumedang City. This study tries to describe the self-concept through social communication in the community's point of view. By looking at the quality of life experienced by the people of Cikondang Village, it can be understood what aspects can affect the quality of community life. This study uses interview techniques to two people of different ages, one male with the initials MY who is still a teenager and one woman with the initials AW who is old. The interview technique was carried out in an unstructured manner using interview guidelines, an informal one-time interview process with an average duration of 30 minutes. Interviews were conducted at home according to the subject' s willingness to be interviewed. These two subjects explain a little about ways in building self-concept such as, how to implement self-concept in the planning process, how to implement self-concept in the implementation process and how to implement self-concept in the assessment process. The results of this study indicate that the process of building self-concept through social communication in Cikondang Village, Sumedang City refers to planning, implementation, assessment and steps which in fact are through theories applied by the community.